Opportunities and Challenges to Realize a Law-Aware Village - Resmaya Agnesia Mutiara Sirait; Yenny Aman Serah; Adhytia Nugraha (Universitas Muhammadiyah Palu, 2023)
Efforts to build legal awareness of rural communities have long been made for the welfare of the community. Carrying out the achievement of community legal awareness towards a legally aware village/village will find challenges and opportunities. The challenges and opportunities of realizing a legally aware village in this are associated with the press perspective of Lawrence M Friedman's theory, namely the theory of the legal system, namely aspects of the substance, structure, and culture of the law. The method used in this study uses a qualitative method with a sociological approach (social, legal approach) through questionnaires, interviews, and discussions with relevant stakeholders. The results of this study explain that the facts show that the achievement of coaching in legal awareness and the process of realizing a legally aware village is still very low. This study revealed that there were challenges in realizing a law-conscious village, namely low legal awareness regarding early marriage and the lack of legally aware family groups (kadarkum) in rural communities. However, it does not rule out the possibility that behind the challenges faced, there are also opportunities obtained by the involvement of students in the Merdeka Belajar Kampus Merdeka (MBKM) program, which is organized by Kementerian Pendidikan dan Kebudayaan, Riset dan Teknologi (Kemendikbudristek) as a companion for rural communities to helping to realize a law-conscious village. Researchers recommend further assessment actions as outlined in two policy texts.